The therapeutic potential of RORγ modulators in the treatment of human disease - Chang, Mi Ra (J Exp Pharmacol, 2012)
Nuclear receptors (NR) are ligand-regulated transcription factors that bind DNA in proximity to their target genes and exert their effects as a result of binding by small molecule ligands such as sterols, lipids, fatty acids, retinoids, and steroid hormones. The retinoic acid receptor-related orphan receptors or RORs (NR1F1–NR1F3) are nuclear receptors that regulate multiple cellular processes, including metabolism, cellular differentiation, and apoptosis, in a range of tissues and organs. These receptors bind as monomers to ROR response elements commonly called ROREs present in promoter regions of target genes and tether chromatin remodeling enzymes, facilitating recruitment of transcription machinery. Several recent reports have highlighted the potential role for RORs in human disease, and more importantly, studies have demonstrated that these receptors can be modulated by exogenous synthetic ligands, paving the way for development of novel therapeutics. Here we review the current status of synthetic ligand development as well as the structural aspects governing modulation of ROR signaling pathways as they relate to metabolic diseases and autoimmune disorders.